The Level of Lecturers’ Understanding of the Madani Concept in Teaching and Learning at Universiti Selangor - Liana Ab Latif; Nursyahirah Wahidah Masrom; Muhammad Daoh; Hafizah Kusnek@Khusni (Utilitas Mathematica, 2025)
Education plays a vital role in shaping the society and culture of a country. In Malaysia, university education has a great responsibility in shaping the thinking and values of the younger generation. To achieve this goal, university lecturers need to understand the basic concepts that are the core of national education with the concept of “Madani”. Therefore, this study aims to assess the level of understanding of lecturers at the University of Selangor Bestari Jaya Campus about the concept of Madani. In addition, this study also examined the lecturers' approach to the application of Madani values in teaching and learning. This study also focused on the challenges faced by lecturers in the application of Madani concept. This study used a quantitative approach by using a questionnaire instrument and distributed it to all lecturers at the University of Selangor Bestari Jaya Campus. The data analysis process for this study used SPSS software. The study findings showed that the majority of lecturers have understood the concept of Madani. However, the majority of lecturers also agreed that they face challenges and constraints in applying the concept of Madani in teaching and learning. Therefore, it is hoped that this study can provide a more comprehensive and in-depth picture of the application of the Madani concept in teaching and learning